Diversity regimes : why talk is not enough to fix racial inequality at universities - Thomas, James M., 1982- (American campus., 2020)
"In Diversity Regimes, James M. Thomas uncovers a complex combination of meanings, practices, and actions that work to institutionalize universities' commitments to diversity, but in doing so obscure, entrench, and even magnify existing racial inequalities. Drawing on two years of ethnographic field work at so-called "Diversity University," Thomas provides new insights into the social organization of multicultural principles and practices"--Publisher's description